A meta-analysis of the ecological and evolutionary drivers of metabolic rates in brachyuran crabs. Issue 2 (4th March 2018) - Griffen, Blaine D.; Sipos, Tori
Abstract: Metabolic rates provide an estimate of the cost of living for different organisms that can readily be compared across species to provide an estimate of their relative requirements for survival. As such, metabolic rates have been measured for decades on a wide range of organisms. Here, we review published estimates of metabolic rates for brachyuran crabs, a ubiquitous and ecologically and economically important group of consumers. Consistent with ecological theory and results in many other groups of animals, and after controlling for phylogenetic relationships, crab metabolic rates scale with body mass with a scaling exponent of 0.65. Similarly, as with other groups of poikilotherms, crab metabolic rates increase strongly with temperature, with a Q10 of 1.26. Additionally, we found that metabolic rates were correlated with ecological niche, varying with both the diet strategy and the habitat occupied. These results help clarify the relative risk to crabs from environmental changes that impose metabolic stress, including climate change and the proliferation of hypoxic zones.